2021
DOI: 10.4103/aer.aer_157_21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postoperative Pain and Analgesia Requirement among Diabetic and Nondiabetic Patients undergoing Lower Limb Fracture Surgery – A Prospective Observational Study

Abstract: Background: Diabetic patients usually experience neuropathic pain and have a decreased response to opioids. Fractures are acute conditions and as such, they are very painful. No data is available related to fracture and postoperative pain in diabetics. Aim: This study was conducted to evaluate postoperative pain and analgesics requirement among diabetic and nondiabetic patients undergoing lower limb fracture surgery and the effect of glycosylated hemoglobin (HbA1c) on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Future studies should evaluate if years of exposure (i.e., time from diagnosis) better predicts the increased odds of POU than specific diagnosis (DMI vs DMII). Similarly, the degree of hyperglycemia over time may partially mediate this effect, and the interaction of degree of elevation in hemoglobin A1C and time over which the patients has been exposed to that hyperglycemia (time since diagnosis) may ultimately prove better at predicting individual risk of POU than the specific diagnosis [ 35 ]. These results suggest that in the same way we appreciate diabetes as a systemic condition impairing the vascular system, the peripheral nervous system, the kidneys and retinas, we need to appreciate an effect on pro-nociceptive components of the sensory nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should evaluate if years of exposure (i.e., time from diagnosis) better predicts the increased odds of POU than specific diagnosis (DMI vs DMII). Similarly, the degree of hyperglycemia over time may partially mediate this effect, and the interaction of degree of elevation in hemoglobin A1C and time over which the patients has been exposed to that hyperglycemia (time since diagnosis) may ultimately prove better at predicting individual risk of POU than the specific diagnosis [ 35 ]. These results suggest that in the same way we appreciate diabetes as a systemic condition impairing the vascular system, the peripheral nervous system, the kidneys and retinas, we need to appreciate an effect on pro-nociceptive components of the sensory nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research reported diabetes as a risk factor for POU [ 10 , 36 40 ]. However, most studies did not differentiate outcomes between DMI and DMII patients, and our findings further highlight disparities among diabetic subgroups warranting further investigation.…”
Section: Discussionmentioning
confidence: 99%